Mitochondrial nucleoid clusters protect newly synthesized mtDNA during Doxorubicin- and Ethidium Bromide-induced mitochondrial stress - Alán, Lukáš; Špaček, Tomáš; Pajuelo Reguera, David; Jabůrek, Martin; Ježek, Petr (Toxicology and applied pharmacology, 2016)
Mitochondrial DNA (mtDNA) is compacted in ribonucleoprotein complexes called nucleoids, which can divide or move within the mitochondrial network. Mitochondrial nucleoids are able to aggregate into clusters upon reaction with intercalators such as the mtDNA depletion agent Ethidium Bromide (EB) or anticancer drug Doxorobicin (DXR). However, the exact mechanism of nucleoid clusters formation remains unknown. Resolving these processes may help to elucidate the mechanisms of DXR-induced cardiotoxicity. Therefore, we addressed the role of two key nucleoid proteins; mitochondrial transcription factor A (TFAM) and mitochondrial single-stranded binding protein (mtSSB); in the formation of mitochondrial nucleoid clusters during the action of intercalators. We found that both intercalators cause numerous aberrations due to perturbing their native status. By blocking mtDNA replication, both agents also prevented mtDNA association with TFAM, consequently causing nucleoid aggregation into large nucleoid clusters enriched with TFAM, co-existing with the normal nucleoid population. In the later stages of intercalation (>48h), TFAM levels were reduced to 25%. In contrast, mtSSB was released from mtDNA and freely distributed within the mitochondrial network. Nucleoid clusters mostly contained nucleoids with newly replicated mtDNA, however the nucleoid population which was not in replication mode remained outside the clusters. Moreover, the nucleoid clusters were enriched with p53, an anti-oncogenic gatekeeper. We suggest that mitochondrial nucleoid clustering is a mechanism for protecting nucleoids with newly replicated DNA against intercalators mediating genotoxic stress. These results provide new insight into the common mitochondrial response to mtDNA stress and can be implied also on DXR-induced mitochondrial cytotoxicity.
Keywords: ethidium; Microtubule-Associated Proteins; mitochondriální DNA; doxorubicin; DNA, Mitochondrial; Nucleoid clusters; poškození DNA; mitochondriální importní komplex; DNA Damage; buňky Hep G2; GTP-fosfohydrolasy; Mitochondrial Precursor Protein Import Complex Proteins; Mitochondria, Liver; Mitochondrial Membrane Transport Proteins; dynaminy; Dynamins; proteiny asociované s mikrotubuly; GTP Phosphohydrolases; DNA vazebné proteiny; nádorový supresorový protein p53; Mitochondrial DNA stress; mitochondriální proteiny; transportní proteiny mitochondriální membrány; Ethidium; Mitochondrial Proteins; jaterní mitochondrie; Ethidium Bromide; lidé; Transcription Factors; Mitochondrial transcription factor A; transkripční faktory; Humans; Hep G2 Cells; DNA-Binding Proteins; Doxorubicin; Tumor Suppressor Protein p53